1994
DOI: 10.1007/bf00232622
|View full text |Cite
|
Sign up to set email alerts
|

The mycotoxin ochratoxin A deranges pH homeostasis in Madin-Darby canine kidney cells

Abstract: Ochratoxin A (OTA) is a nephrotoxin which blocks plasma membrane anion conductance in Madin-Darby canine kidney (MDCK) cells. Added to the culture medium, OTA transforms MDCK cells in a manner similar to exposure to alkaline stress. By means of video-imaging and microelectrode techniques, we investigated whether OTA (1 mumol/liter) affects intracellular pH (pHi), Cl- (Cl-i) or cell volume of MDCK cells acutely exposed to normal (pHnorm = 7.4) and alkaline (pHalk = 7.7) conditions. At pHnorm, OTA increased Cl-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Greger and coworkers demonstrated that in epithelial cells, NPPB added to the extracellular fluid is three orders of magnitude more potent than A9C (Wangemann et al, 1986). Ochratoxin A was also demonstrated to be able to block chloride channels in epithelial cells and shows a structural similarity to NPPB (Wdll et al, 1993;Gekle et al, 1993 (Paulmichl et al, 1993;Gschwentner et al, 1995a). In order to obtain a more precise 2.…”
Section: Discussionmentioning
confidence: 99%
“…Greger and coworkers demonstrated that in epithelial cells, NPPB added to the extracellular fluid is three orders of magnitude more potent than A9C (Wangemann et al, 1986). Ochratoxin A was also demonstrated to be able to block chloride channels in epithelial cells and shows a structural similarity to NPPB (Wdll et al, 1993;Gekle et al, 1993 (Paulmichl et al, 1993;Gschwentner et al, 1995a). In order to obtain a more precise 2.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of those key targets will improve our understanding of mycotoxicosis substantially. Low dose Non competitive inhibition of the Blockade of plasma membrane anion organic anion transport system [7,9] channels and Cl -/HCO 3 -exchange Inhibition of the organic cation [22,28,32, 33] transport system [7] Alterations in cellular pH and ClCell proliferation and hypertrophy homeostasis and of transepithelial H + [10,30] and electrolyte transport [22][23][24]28, 29] Impaired protein reabsorption [2,31] Activation of extracellular signalregulated kinases (ERK 172) [29] Cell dedifferentiation [28,29] High dose Decreased cell viability [7,10,30] Decreased cell viability [6,22,29] Leaky plasma membrane [7,30] Leaky plasma membrane [6,29] Impaired DNA synthesis [7,30] Impaired DNA synthesis [25,29] Impaired protein synthesis [7,31] Impaired protein synthesis [25] Reduced cell growth [7,30] Reduced cell growth [29] Cell detachment and general decrease Cell detachment and general decrease in transport activity [7,21,30,31] in transport activity …”
mentioning
confidence: 99%
“…enzymeregulating messengers) and thereby, leads to the disturbance of cellular signalling and regulatory events (e.g. carrier inhibition [7,28], MAPK activation [29]). Those changes in cellular signalling and/or regulation result in specific changes in cell function and/or phenotype, leading to changes in renal function and finally to the possible disturbance of the whole organism homeostasis.…”
mentioning
confidence: 99%
“…Cells from this mouse proliferate at 33°C in the presence of y-interferon but cease cell division at 37°C in the absence of the y-interferon . There is no difference in the absolute magnitude of the chloride conductance between cells grown in the different conditions, although differences have been found with respect to the effects of the nephrotoxic mycotoxin ochratoxin A which inhibits anion conductances in the renal epithelial MDCK cell line (Gekle et al, 1993 The absence of a dose-dependent relationship for concentrations of up to 10-11 M P1075 and 10-7 M, pinacidil, together with the continued inhibition following drug removal, suggested that these drugs might be irreversible inhibitors of the chloride conductance. This was confirmed by the 16 h incubations with low concentrations of the drugs.…”
Section: Resultsmentioning
confidence: 94%